2021
DOI: 10.1371/journal.pone.0246651
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and preservation of the components of the engulfment. What is beyond representative genomes?

Abstract: Engulfment requires the coordinated, targeted synthesis and degradation of peptidoglycan at the leading edge of the engulfing membrane to allow the mother cell to completely engulf the forespore. Proteins such as the DMP and Q:AH complexes in Bacillus subtilis are essential for engulfment, as are a set of accessory proteins including GerM and SpoIIB, among others. Experimental and bioinformatic studies of these proteins in bacteria distinct from Bacillus subtilis indicate that fundamental differences exist reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…show patterns of extensive loss of sporulation genes. Consistent with the previous observations (59,60), they both lack seven of the nine genes of the SpoIIQ-SpoIIIA complex, retaining only SpoIIQ and SpoIIIAH components. Further, they both lack such widely conserved sporulation genes as spoIIID, bofA, cotQ, safA, yabQ, ypeB, yyaC, yyaD, sleL (yyaH), and gerW (ytfJ) (Table S2, Table S4).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…show patterns of extensive loss of sporulation genes. Consistent with the previous observations (59,60), they both lack seven of the nine genes of the SpoIIQ-SpoIIIA complex, retaining only SpoIIQ and SpoIIIAH components. Further, they both lack such widely conserved sporulation genes as spoIIID, bofA, cotQ, safA, yabQ, ypeB, yyaC, yyaD, sleL (yyaH), and gerW (ytfJ) (Table S2, Table S4).…”
Section: Resultssupporting
confidence: 92%
“…The Erysipelotrichia members C. innocuum and E. ramosum retain only the spoIIIAH and spoIIQ genes. In addition, they possess SpoIVFB and GerM, but lack SpoIIB and SpoIVFA (Table S2, Figure S5B, C), see also reference (60). Six members of the family Planococcaceae show stronger conservation of the SpoIIQ-SpoIIIA complex: in addition to SpoIIIAH and SpoIIQ, they retain SpoIIIAC, SpoIIIAE, and SpoIIIAG components (Fig.…”
Section: Sporulation Onset and Asymmetric Divisionmentioning
confidence: 83%
“…We used this information to search for orthologous sequences of BCLs in bacterial genomes. To this end, we used an approach developed by our group ( Martinez-Amador et al, 2019 ; Soto-Avila et al, 2021 ), in which the first step was the identification of Pfam domains found in the PfamA database ( Mistry et al, 2021 ), whose matrices were used to inspect the amino acid sequences of proteomes downloaded from the KEGG database. Once the Pfam domains were identified, we constructed protein architectures.…”
Section: Methodsmentioning
confidence: 99%
“…These pathways are often arranged as operons ( Egland et al, 1995 ; Porter and Young, 2014 ; Arnold et al, 2021 ). Therefore, instead of considering three upstream and downstream genes, as proposed in our previous work ( Martinez-Amador et al, 2019 ; Soto-Avila et al, 2021 ), we extended the inspection of genes in the genomic context to 10 upstream and 10 downstream genes from the BCL. The protein architectures and the Pfam accession numbers of the genes represented in the genomic context are shown in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation